The Authority of the Serang City Social Service in Overcoming the Urban Poor as a Form of Service and Fulfilling the Basic Rights of the Poor Based on Serang City Regional Regulation Number 3 of 2011 concerning Poverty Alleviation - Mahendra, Muhamad Yusril Ihza (Beleid, 2023)
Overcoming the poor is a policy and program for both the government and local governments as one of the manifestations of the welfare state as stipulated in Article 28C paragraph (1) and Article 34 of the 1945 Constitution of the Republic of Indonesia. Both articles mandate the state's obligation to care for the poor and abandoned children. Data from the Central Bureau of Statistics of Serang City explains that the poor or those under poverty in Serang City as of March 2022 fell from 6.79 percent to 6.12 percent. The number of poor people fell from 47,000 in 2021 to 43,000 in March 2022. There was a decrease of 4,000 people. This indicates that there is an overcoming and fulfillment of the basic rights of the poor carried out by the government and also the Seran City Social Service. The research method used in this research is empirical juridical analysis with data analysis through a qualitative approach using primary data in the form of interviews with Serang City Social Service Officials in the Poor Handling Division. The result of this research is that the Social Service of Serang City in the Poor Handling Division has carried out its authority well as mandated by the Serang City Regional Regulation Number 3 of 2011 concerning Poverty Reduction.